Enterovirus Detection Trends Based on Respiratory Specimens from a Single Tertiary Hospital in Korea (2018–2024): A Retrospective Study Using Multiplex PCR Data - Jeong Su Han; Sung Hun Jang; Jae-Sik Jeon; Jae Kyung Kim (Viruses)
Enteroviruses (EVs) cause broad clinical manifestations, particularly in children. Certain serotypes have been implicated in respiratory infections; however, epidemiological studies analyzing EV circulation based on clinical respiratory specimens are limited in Korea. This retrospective study evaluates EV detection patterns in respiratory specimens to demonstrate their clinical and epidemiological significance as respiratory pathogens in Korea. Respiratory samples collected from outpatient and hospitalized patients with respiratory symptoms at Dankook University Hospital between 2018 and 2024 were analyzed. EV detection patterns were analyzed by year, season, sex, and age. EVs were detected in 303/6292 respiratory specimens. The highest and lowest positivity rates were in 2018 (8.2%) and 2020 (1.6%), likely due to non-pharmaceutical interventions during the COVID-19 pandemic. The highest positivity rates were in summer and autumn, and in children aged 2–11 years and infants aged 0–1 years. EV positivity did not differ significantly between sexes. Significant differences were identified across years, seasons, and age groups. EVs can be detected in respiratory specimens from symptomatic patients and exhibit a marked seasonal distribution and elevated positivity rates in pediatric populations. Hence, EVs may act as atypical respiratory pathogens, underscoring the need for integrated public health surveillance and seasonal prevention strategies.